Health Promotion Model untuk Meningkatkan Perilaku Pencegahan Penularan Tuberkulosis - Rumakey, Ratna Sari; Tukiman, Suryanti (FORIKES, 2022)
Tuberculosis is an infectious disease of the top 10 causes of death in the world. The prevalence of pulmonary tuberculosis in Maluku Province is still high, so it must receive serious treatment. This study aims to determine the effectiveness of the health promotion model on behavior to prevent pulmonary tuberculosis transmission at the Hitu Health Center and Hila Health Center, Central Maluku. The design of this study was a non-randomized pretest-posttest with control group, which involved 15 respondents for each group, who were selected by purposive sampling technique. Health education with the health promotion model was carried out and then its impact was evaluated including: knowledge, attitudes and actions. The results showed that the p-value for each effect was: knowledge = 0.00, attitude = 0.01 and action = 0.00. It was concluded that health education based on the health promotion model was effective in increasing knowledge, attitudes and prevention of tuberculosis transmission.Keywords: pulmonary tuberculosis; health promotion models; knowledge; attitude; preventive measure ABSTRAK Tuberkulosis merupakan penyakit menular dari 10 penyakit teratas penyebab kematian di dunia. Prevalensi tuberkulosis paru di Provinsi Maluku masih tinggi, sehingga harus mendapatkan penanganan yang serius. Penelitian ini bertujuan untuk mengetahui efektifitas health promotion model terhadap perilaku pencegahan penularan tuberkulosis paru di Puskesmas Hitu dan Puskesmas Hila, Maluku Tengah. Rancangan penelitian ini adalah non randomized pretest-posttest with control group, yang melibatkan 15 responden untuk masing-masing kelompok, yang dipilih dengan teknik purpossive sampling. Pendidikan kesehatan dengan health promotion model dilakukan lalu dievaluasi dampaknya meliputi: pengetahuan, sikap dan tindakan. Hasil penelitian menunjukkan nilai p untuk masing-masing dampak yaitu: pengetahuan = 0,00, sikap = 0,01 dan tindakan = 0,00. Dismpulkan bahwa pendidikan kesehatan berbasis health promotion model efektif untuk meningkatkan pengetahuan, sikap dan tindakan pencegahan penularan tuberkulosis.Kata kunci: tuberkulosis paru; health promotion model; pengetahuan; sikap; tindakan pencegahan